Pengaruh Model Pembelajaran Self Directed Learning (SDL) terhadap Kemampuan MenulisTeks Anekdot Siswa Kelas X SMK Negeri 1 Lubuk Pakam - Putri Suci Ramadhani; Susy Deliani Deliani; Sri Muliatik (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to determine the significant effect of the use of the Self Directed LearningModel on the ability to write anecdotal texts of class X students of SMK Negeri 1 LubukPakam.Thetypeofresearchusedisquantitativeresearchwithatwogrouppretest-posttestdesign. The population in this study were 68 class X students of SMK Negeri 1 LubukPakam. The instrument in this study the researcher used a test. Based on the results of thestudy, the ability to write anecdotal texts before using the Self Directed Learning learningmodelobtainedanaverageof55andastandard deviationof12.90994withadistributionof pre-test data tendencies included in the poor category. The ability to write anecdotaltexts after using the Self Directed Learning learning model averaged 83.1 and a standarddeviation of 7.021396 with a distribution of post-test data tendencies included in the verygoodcategory.Basedontheresultsofthehypothesistesting,tcountttable(10.8282.03452)wasobtained.ThismeansthatHoisrejectedandHaisaccepted,whichmeansthatthereisaninfluenceoftheSelfDirectedLearninglearningmodelontheabilitytowriteanecdotaltextsinclassXstudentsofSMKNegeri1LubukPakam.